Possibilities of Performance Audit to Increase the Transparency of Activities in the Municipality - Liukinevičienė, Laima; Jokubauskienė, Audra (Socialiniai tyrimai, 2021)
The article analyzes the implementation of the transparency principle in implementing the performance audit in the municipality. The performance audit is qualified as a specific control function in order to objectively assess the functionality of public sector entities in terms of economy, efficiency and effectiveness, initiating operational and governance advancement. It is important to investigate this object in municipalities due to the following factors: 1) according to the assessment of the transparency of Lithuanian municipalities published in 2019 by “Transparency International” of the Lithuanian branch, municipalities have become more transparent as well as the recommendations were provided to municipalities; 2) Recent research conducted in foreign countries shows broader audit opportunities for initiating positive change in organizations. The aim of the research: having established the principle of transparency as one of the most important indications of good governance, to provide for the possibilities of increasing the transparency of municipal activities during the performance audits. Research methods: analysis of scientific literature, the content of documents, qualitative analysis of the expert interview and the content of the material collected during it, and categorization. The analyzed sources show how during these two decades of developing the theoretical concept of good governance the importance of the principle of transparency has grown, it has become one of the most important features of good governance; the concept of implementing transparency in public sector organizations has developed as well. Today, the principle of operational transparency is implemented both through strictly formalized government activities and by involving citizens in public governance that requires much honesty, competencies and non-traditional solutions of civil servants. How can a performance audit contribute to this? In order to gain new insights, experts were interviewed: researchers and practicians. Recommendations from external evaluators on transparency in municipalities were used to develop the guidelines for the expert interviews. The research revealed that in municipalities it is important to create greater opportunities for the citizens to participate in monitoring and involvement in decision-making. The directions for increasing the transparency of municipal activities through performance audits that have been highlighted by experts are as follows: 1) periodic performance transparency audits by including constantly updated performance transparency criteria in the audit; 2) creation of a non-corruption organization; 3) increasing the transparency of budgeting and implementation; 4) submission of budget reports with audit conclusions; 5) attention to the clarity of the content of audit reports, diversity of accessibility; 6) periodic monitoring of the effectiveness of audit findings; 7) integration of audits of social responsibility activities into other forms of performance evaluation, thus not increasing the number of audits but seeking greater integration of the principle of transparency. The experts proposed transparency evaluation criteria that can be easily integrated into the evaluation process.